PENGARUH DAYA TARIK IKLAN, SOSIAL MEDIA, DAN PENEMPATAN PRODUK TERHADAP KESADARAN MEREK MASKER SENSI DI PALEMBANG SQUER MALL - Agung Bambang Saputra; Dian Utari; Muhammad Furqon; Miftahul Jannah (P3M STIE Mulia Darma Pratama, 2026)
The use of masks is part of a comprehensive series of prevention and control measures that can limit the spread of certain viral respiratory diseases, including COVID-19. Masks can be used either to protect a healthy person (worn to protect themselves when in contact with an infected person) or to control the source (worn by an infected person to prevent further transmission). Masks play an important role in protecting yourself from the corona virus. The objectives of this study are: 1) To determine the effect of the attractiveness of advertising, social media, and product placement partially on the awareness of the Sensi Mask brand in Palembang Squer Mall. 2) To find out the effect of the attractiveness of advertising, social media, and product placement simultaneously on the awareness of the Sensi Mask brand at Palembang Squer Mall. Data analysis method used in this research is verification method. The results showed that the t-test (partially) can be explained: The advertising attractiveness variable (X1) has a significant effect on brand awareness (Y), the value of tcount (3.632) > ttable (1.679) and a significant value of 0.000 <0.05 means Ho is rejected and Ha accepted. The social media variable (X2) has a significant effect on brand awareness (Y). The value of tcount (3.817) > ttable (1.679) and a significant value of 0.000 <0.05 means that Ho is rejected and Ha is accepted. The product placement variable (X3) has a significant effect on brand awareness (Y). The value of tcount (2,983) > ttable (1,678) and a significant value of 0.000 <0.05 means Ho is rejected and Ha is accepted. The results of the F test (simultaneously), the results obtained are Fcount (25.934) > Ftable (2.574) and a significant value of 0.000 <0.05, meaning Ho is rejected and Ha is accepted, meaning that there is a simultaneous effect of Advertising Attractiveness variable (X1), Social Media (X2), and Product Placement (X3) on Brand Awareness (Y) of Sensi Masks at Palembang Squer Mall. The coefficient of determination of Adjusted R Square obtained is 0.797 (79.7%) meaning that the variables of Advertising Attractiveness (X1), Social Media (X2), and Product Placement (X3) explain Brand Awareness (Y) of 79.7% while the rest 20.3% (100% – 79.7%) can be explained by other variables not examined in this study and can then be further investigated by other researchers.